Sustainable Urban Mobility: A Comparative Analysis of China-Nigeria Green Transportation Policies and Their Impact on Smart City Development and Carbon Reduction Initiatives - Esangbedo, Caroline; Olurin, Olawunmi Dorcas (Sustainability Science and Resources, 2025)
This study critically examines the comparative effectiveness of green transportation policies and blockchain implementation in China and Nigeria, addressing the urgent challenges of rapid urbanization and environmental sustainability. Grounded in Strategic Niche Management theory, the research explores how policy frameworks, technological readiness, and sociocultural factors shape sustainable urban mobility outcomes. Employing a mixed-methods approach, the study analyses data from 400 respondents across four major cities, complemented by in-depth interviews with key stakeholders. Findings reveal significant disparities in policy effectiveness and blockchain integration between the two countries, with China demonstrating superior performance across most metrics. However, unexpected areas of convergence emerged, particularly in Nigeria's mobile payment integration and blockchain adoption among younger urban populations. The study challenges conventional assumptions about technological gaps between developed and developing nations, highlighting the potential for targeted policy interventions to accelerate progress in specific niches. A non-linear relationship between smart contract adoption and carbon reduction outcomes underscores the complexity of implementing sustainable transportation solutions. The research contributes to the evolving discourse on policy transfer and technological leapfrogging in developing economies, while emphasizing the need for context-specific strategies that account for local institutional capacities and cultural factors. These findings have significant implications for policymakers and practitioners, advocating for adaptive management approaches and international collaboration to foster more effective, equitable, and sustainable urban transportation systems in diverse urban contexts.